Peningkatan Pendapatan Melalui Kompetitivitas Pelaku Usaha Mikro dan Kecil - Erza, Osni; Sirait, Koramen H; Nilawati, Yuana Jatu (PT. Cendekia Sapta Indonesia, 2024)
This Community Service (PkM) aims to increase the income of business actors by providing motivation and knowledge to Micro and Small Enterprises regarding product competitiveness, determining the cost of goods sold, and marketing strategies in the post-Covid 19 Pandemic. The PkM method is carried out by means of counseling and training held at the Azalea Grand Depok City location. The results of monitoring and interviews show that some of the Micro and Small Enterprises participants can market their products well and have competitiveness in the market, both in conventional and online markets and can expand the marketing of their products by participating in various bazaars. The expected output targets are that business actors have been able to make products of better quality, have a wider variety of products, market them more broadly, be more creative and can increase revenue.